Factores que inciden en la enfermedad diarreica aguda en niños/as menores de 5 años atendidos en el Subcentro de Salud El Aguador en el segundo semestre del 2012. - Peralta Moreno, Juan C. (2013)
The acute diarrheal disease is one of the public health problem more important in the world the disease affects all age groups, however the most vulnerable are children under 5 years, constituting in addition a problem with a high morbidity and mortality worldwide especially in developing countries.